Evaluation of the design and implementation of municipal ice cleat distribution programs for the prevention of ice-related fall injuries among older adults in Sweden. - Robin Holmberg (Public Library of Science (PLoS), 2021)
Introduction The risk for outdoor falls tends to increase during winter due to icy road conditions. Several Swedish municipalities have introduced programs that provide their senior citizens with a pair of ice cleats in an attempt to tackle this problem. In this paper, we perform a process evaluation to identify potential barriers to the success of these programs and analyze the logic of their design. Methods We sent a survey to all 290 Swedish municipalities to collect data on the characteristics of ice cleat distribution programs. We also performed focus-group interviews with older adults to gain insight into their thoughts about ice cleat programs. We synthesized our data with existing literature on ice cleats and behavior change theory to populate a logic model to identify and analyze hidden assumptions and potential flaws using program theory analysis. Results On average, about 40% of the eligible population living in the intervention municipalities collected a pair of ice cleats. While we identified some other, but mostly minor, barriers to implementation, the main barrier appears to be a lack of scale (i.e., insufficient procurement and distribution of ice cleats), as 90% of all purchased ice cleats were eventually distributed. While previous research suggests that ice cleats can decrease injury risks if worn, we find that there is limited evidence on the effects of distribution on ice cleat use. Our interviewees emphasized the potential utility of ice cleats for staying safe and active during winter but stressed that ice cleats need to be user-friendly and of high-quality to increase the likelihood that a distribution program encourages behavior change. Conclusion Existing ice cleat distribution programs appear to have reached a meaningful share of the targeted population. Additional research is required to assess their effects on ice cleat use and injury rates.